HUBUNGAN KUALITAS TIDUR DENGAN FUNGSI KOGNITIF PADA PASIEN STROKE ISKEMIK USIA PRODUKTIF - Sarah Dewi Permata Sari (2023)
Stroke is a disease that can be suffered by humans at any time regardless of age. Usually stroke occurs without realizing it and occurs progressively. The prevalence in the world and in Indonesia shows that ischemic stroke is more prevalent than hemorrhagic stroke. Stroke in productive age has a more severe impact and needs more attention, affecting the patient's physical activity and work productivity. Lifestyle risk factors such as poor sleep quality can worsen the patient's condition. In ischemic stroke patients, neurological function disorders that often occur are cognitive function disorders. This study is to determine the relationship between sleep quality and cognitive function in ischemic stroke patients of productive age. This study is a quantitative study with a cross sectional approach on 80 respondents with purposive sampling method. Data collection using sleep quality questionnaire (PSQI) and cognitive function (MoCA-Ina). The results of the chi-square test showed no relationship between sleep quality and cognitive function in ischemic stroke patients of productive age with a p-value of 0.052>0.05 and an OR value of 3.309. Although poor sleep quality has the possibility of developing cognitive impairment in ischemic stroke patients of productive age, this study could not establish a statistically significant relationship.